Program uroczystości "Święta Morza" w Gdyni od dnia 23.6. do 29.6. 1947 r. / Henryk Zakrzewski. - Zakrzewski, Henryk (1897-?).; Święto Morza (1947). (Gdynia : [s.n.], 1947)
Afisz z programem uroczystości.
Keywords: Święta -- Polska -- Gdynia -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- źródła